2021
DOI: 10.1101/2021.04.14.439642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MonomorphicTrypanozoon: towards reconciling phylogeny and pathologies

Abstract: Trypanosoma brucei evansi and Trypanosoma brucei equiperdum are animal infective trypanosomes conventionally classified by their clinical disease presentation, mode of transmission, host range, kDNA composition and geographic distribution. Unlike other members of the subgenus Trypanozoon, they are non-tsetse transmitted and predominantly morphologically uniform (monomorphic) in their mammalian host. Their classification as independent species or subspecies has been long debated and genomic studies have found t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…From our data, the complete lack of PAG3 combined with the monomorphic phenotype found in all strains of T. evansi, that we looked at, and some strains of T. equiperdum suggest a strong link between the function of this gene and differentiation of the bloodstream forms of Trypanozoon parasites. A recent analysis of the relationships between T. brucei, T. evansi and T. equiperdum, using genome sequencing data, demonstrated the presence of two clades of T. evansi (Type A and B) (Cuypers et al, 2017;Oldrieve et al, 2021). A detailed look at a Type B strain (MU10) in the NCBI Sequence Read Archive, we found that the PAG3 gene is probably present but appears to have indels and frameshifts which may possibly render it inactive.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…From our data, the complete lack of PAG3 combined with the monomorphic phenotype found in all strains of T. evansi, that we looked at, and some strains of T. equiperdum suggest a strong link between the function of this gene and differentiation of the bloodstream forms of Trypanozoon parasites. A recent analysis of the relationships between T. brucei, T. evansi and T. equiperdum, using genome sequencing data, demonstrated the presence of two clades of T. evansi (Type A and B) (Cuypers et al, 2017;Oldrieve et al, 2021). A detailed look at a Type B strain (MU10) in the NCBI Sequence Read Archive, we found that the PAG3 gene is probably present but appears to have indels and frameshifts which may possibly render it inactive.…”
Section: Discussionmentioning
confidence: 61%
“…This might support the notion that the genotypes of T. equiperdum have polyphyletic origins. This is supported by the studies of Oldrieve et al (2021) who demonstrated, by genome analysis, that there is indeed more than one clade of T. equiperdum in the strains that they look at. Unfortunately, their strains do not correspond to our strains.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations